RESPONSE OF WEANER RABBITS TO GRADED LEVELS OF SUN-DRIED BOVINE RUMEN CONTENT - Emmanuel, U. N.; Muhammad, A. S.; Sani, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to determine the response of weaner rabbits to graded levels of sun-dried bovine rumen content (SDBRC). A total of forty (40) weaner rabbits were randomly allotted to five dietary treatments, replicated four times in a Completely Randomized Design, in which sun-dried bovine rumen content partially replaced wheat offal at 0, 30, 35, 40 and 45%, and designated as diet 1, 2, 3, 4 and 5 respectively. The results of the study revealed that, performance parameters such as the total weight gain (659.63 to 787.38g), total feed intake (3450.40 to 3672.80g), feed conversion ratio (4.73 to 5.32) and feed efficiency (0.19 to 0.22) were not significantly affected by the dietary treatments. Similarly carcass parameters showed no significant difference except for abdominal fat which was significantly (P<0.01) affected, with the highest (1.02%) on diet 1 and the lowest (0.34%) on diet 3. Faecal sample analysis indicated a significant (P<0.01) difference for crude protein (89.34 to 91.40%), crude fibre (83.65 to 86.13%), ash (93.00 to 94.92%) and ether extract (98.28 to 98.94%), while dry matter and nitrogen free extract were not significantly influenced by the dietary treatments. Haematological and serum biochemical indices showed no significant effect across the dietary treatments except for urea (3.52 to 8.64mmol/l) which showed a significant (P<0.01) response to dietary treatments. Total feed cost reduced as the level of sun-dried bovine rumen content increased, and the least total feed cost (₦1782.37) was recorded for rabbits fed diet 5 (45% SDBRC). Feed cost per kg gain ranged from ₦2475.51 to ₦2758.74 on diets 5 and 4 respectively. In terms of cost saving, diet 5 had the highest (₦137.63) with a percent cost saving of 5.27%. Based on the results obtained from this study, it can be concluded that sun-dried bovine rumen content can best replace wheat offal at 45% level in the diets of weaner rabbits with comparative performance, carcass characteristics, haematological and serum biochemical indices to the control. Diet 5 (45% SDBRC) also had the cost benefit (₦137.63) and is therefore recommended for rabbit production.